Real-World Clinical Experience of Tralokinumab in a Tertiary Centre: An Alternative for Patients with Conjunctivitis on Dupilumab? - Neenu Sebastian; Omar Chircop; Tim H. Clayton; Firas C. Kreeshan; Hamish J. A. Hunter; Richard B. Warren (Dermatology and Therapy)
Abstract Introduction Tralokinumab, a human IgG4 monoclonal antibody that inhibits the IL-13 pathway, is approved for the treatment of atopic dermatitis. However, real-world data are lacking and are needed to inform its efficacy and safety in broader populations. Methods This retrospective study reviewed the Eczema Area and Severity Index (EASI) and Dermatology Life Quality Index (DLQI) at baseline and 16–20 weeks of 39 consecutive patients who received subcutaneous tralokinumab at the label dose in a tertiary centre. Results Twenty-nine out of 39 patients had an EASI score recorded after 16–20 weeks. At 16–20 weeks, 65.5% (19/29) of patients achieved EASI 50, 37.9% (11/29) achieved EASI 75, and 27.8% (9/29) achieved EASI 90. DLQI was reduced by an average of − 10.4 points at 16–20 weeks. No serious adverse events were reported. Ocular adverse events were reported in 25.6% (10/39) of the cohort but did not lead to treatment discontinuation. Six out of seven patients that previously experienced conjunctivitis with dupilumab had no recurrence with tralokinumab. Conclusion Our study supports using tralokinumab in atopic dermatitis with similar real-world efficacy to that shown in clinical trials. Tralokinumab offers an alternative for patients failing dupilumab because of conjunctivitis.